Willful child : wrath of Betty - Erikson, Steven (Erikson, Steven. Willful Child., 2016)
In the continuing adventures of the starship A.S.F. Willful Child, not-terribly-bright but exceedingly cock-sure Captain Hadrian Sawback and his motley crew embark on another rollicking ride through the infinite vastness of interstellar space.